The ikaite to calcite transformation: Implications for palaeoclimate studies. (1st October 2022) - Vickers, Madeleine L.; Vickers, Martin; Rickaby, Rosalind E.M.; Wu, Han; Bernasconi, Stefano M.; Ullmann, Clemens V.; Bohrmann, Gerhard; Spielhagen, Robert F.; Kassens, Heidemarie; Pagh Schultz, Bo; Alwmark, Carl; Thibault, Nicolas; et al.
Abstract: Marine sedimentary ikaite is the parent mineral to glendonite, stellate pseudomorphs found throughout the geological record which are most usually composed of calcite. Ikaite is known to be metastable at earth surface temperatures and pressures, readily breaking down to more stable carbonate polymorphs when exposed to warm (ambient) conditions. Yet the process of transformation of ikaite to calcite is not well understood, and there is an ongoing debate as to the palaeoclimatic significance of glendonites in the geological record. This study uses a combination of techniques to examine the breakdown of ikaite to calcite, outside of the ikaite growth medium, and to assess the palaeoclimatic and palaeoenvironmental significance of stable and clumped isotope compositions of ikaite-derived calcite. Powder X-ray diffraction shows that ikaite undergoes a quasi- solid-state transformation to calcite during heating of samples in air, yet when ikaite transforms under a high temperature differential, minor dissolution-recrystallisation may also occur with the ikaite structural waters. No significant isotopic equilibration to transformation temperature is observed in the resulting calcite. Therefore, in cases of transformation of ikaite in air, clumped and stable isotope thermometry can be used to reconstruct ikaite growth temperatures. In the case of ancient glendonites, where transformation of the ikaite occurred in contact with the interstitial waters of the host sediments over unknown timescales, it is uncertain whether the reconstructed clumped isotope temperatures reflect ikaite crystallisation or its transformation temperatures. Yet clumped and stable isotope thermometry may still be used conservatively to estimate an upper limit for bottom water temperatures. Furthermore, stable isotope along with element/Ca ratios shed light on the chemical environment of ikaite growth. Our data indicate that a range of (bio)geochemical processes may act to promote ikaite formation at different marine sedimentary sites, including bacterial sulphate reduction and anaerobic oxidation of methane. The colours of the ikaites, from light brown to dark brown, indicate a high organic matter content, favouring high rates of bacterial sulphate reduction as the main driver of ikaite precipitation. Highest Mg/Ca ratios are found in the most unstable ikaites, indicating that Mg acts to destabilise ikaite structure.